THE EFFECT OF SERVANT LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: THE ROLE OF TRUST IN LEADER AS A MEDIATION AND PERCEIVED ORGANIZATIONAL SUPPORT AS A MODERATION - Diah Astrini Amir (Journal of Leadership in Organizations, 2019)
Current organizational behavior studies emphasize the importance of the human aspect. Therefore, leadership as a study of organizational behavior needs to focus on human aspects. The servant leadership (SL) popularized by Greenleaf in 1970 was in line with the idea. SL is explicitly defined as leadership that focuses on serving the needs of subordinates (human aspects). SL is believed to affect subordinate positive behavior which is indicated by organizational citizenship behavior (OCB). However, in the effect of SL on OCB, there is still debate over whether both of them have a direct or indirect impact. The role of organizational context is also not considered in previous studies. This study aims to examine the role of trust in leaders (TIL) as a mediating variable and perceived organizational support (POS) as a moderating variable on the effect of SL on OCB. A total of 238 respondents were collected in the current study in various regions of Indonesia. The results showed that SL had a significant positive effect on OCB. POS was also reported to significantly moderate the effect of SL on OCB. In addition, it was unexpectedly reported that TIL did not mediate the effect of SL on OCB. POS also reported not moderating the effect of SL on OCB through TIL. The arguments in explaining these results are discussed in more detail in the discussion section of this article.